CRISPR–Cas Systems Associated with Electrolyte-Gated Graphene-Based Transistors: How They Work and How to Combine Them - Pierre Guermonprez; Pierre Nioche; Louis Renaud; Nicolas Battaglini; Sébastien Sanaur; Eric Krejci; Benoît Piro (Biosensors)
In this review, recent advances in the combination of CRISPR–Cas systems with graphene-based electrolyte-gated transistors are discussed in detail. In the first part, the functioning of CRISPR–Cas systems is briefly explained, as well as the most common ways to convert their molecular activity into measurable signals. Other than optical means, conventional electrochemical transducers are also developed. However, it seems that the incorporation of CRISPR/Cas systems into transistor devices could be extremely powerful, as the former provides molecular amplification, while the latter provides electrical amplification; combined, the two could help to advance in terms of sensitivity and compete with conventional PCR assays. Today, organic transistors suffer from poor stability in biological media, whereas graphene materials perform better by being extremely sensitive to their chemical environment and being stable. The need for fast and inexpensive sensors to detect viral RNA arose on the occasion of the COVID-19 crisis, but many other RNA viruses are of interest, such as dengue, hepatitis C, hepatitis E, West Nile fever, Ebola, and polio, for which detection means are needed.